(untitled) (Journal of the College of Basic Education, 2025)
The poet Abdullah ibn al-Mu’tazz (d. 296 AH) lived during the second Abbasid era, and his life was marked by both suffering and pain, as well as living in the palaces of caliphs and experiencing homelessness. Nevertheless, the poet managed to win the favor of everyone in the palace and was able to employ the word "tears" as a central theme in his poetry. The term "tears" recurs in his work, with its meanings varying according to the poetic subject and context.To explore these meanings, we divided the research into an introduction and three sections. In the introduction, we provided a brief overview of his life. In the first section, we discussed the significance of tears in the theme of nostalgia. In the second section, we examined the significance of tears in the theme of chaste love. In the third section, we explained the significance of tears in the theme of love for young boys.The study concluded that the poet wept over the departure of women, their separation from him, and their rejection, describing his tears as he ached for their closeness. He also cried in his poetry about love for boys, which may be attributed to several reasons, including the influence of the poet Abu Nuwas. Both poets were deprived of children, establishing a connection between the tears in the poetry about boys and the poet’s life. At times, tears symbolize sorrow, while at other times, they symbolize joy. The poet pours into this term all the richness of life he experienced—playfulness, sadness, wealth, and deprivation. Thus, we find tears of repentance, tears of revelation, tears of redemption, and tears flowing freely.